Deontological Ethics of Desmond Doss in Booton Herndon’s Redemption at Hacksaw Ridge - Pendong, Richard; Rorintulus, Olga; Lolowang, Imelda (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
Redemption at Hacksaw Ridge was written by Booton Herndon. The book, which is based on the true story of American Army medic Desmond Doss during World War II, emphasizes Doss' strong moral principles, which prevented him from carrying a weapon or taking part in acts of violence. This study intends to examine the deontological ethics embodied by Doss in the book, emphasizing his moral commitments, ethically grounded decision-making, and the consequences of his actions during the conflict. Sigmund Freud's psychological theory and a qualitative approach are used in the study to pinpoint three important subtopics in Doss's character: morality, duty, and human rights. The results highlight Doss's steadfast adherence to his moral principles and personal religion despite strong peer pressure. As he carried out his front-line medic duties, he never wavered from his non-violent principles. According to the research, Desmond Doss's story from Redemption at Hacksaw Ridge offers a compelling illustration of upholding moral principles in the face of adversity. It highlights the significance of keeping moral standards in place even in the face of strong opposition, demonstrating that morality and bravery can coexist in the real world.